Which is the top player for the cardiovascular safety? ibrutinib vs. obinutuzumab in CLL - Mascolo, Annamaria; Di Napoli, Raffaella; Balzano, Nunzia; D’Alessio, Elena; Izzo, Imma; Rossi, Francesco; Paolisso, Giuseppe; Capuano, Annalisa; Sportiello, Liberata (Frontiers in Pharmacology, 2023)
Ibrutinib, a Bruton's tyrosine kinase (BTK) inhibitor, is authorized for the treatment of chronic lymphocytic leukemia (CLL). This study aims to explore the cardiac safety profile of ibrutinib in comparison with obinutuzumab. A retrospective pharmacovigilance study was conducted on data retrieved from the European pharmacovigilance database (Eudravigilance) from January 1st, 2014 to September 30th, 2022. To compare the reporting frequency of cardiovascular events among ibrutinib, obinutuzumab, and the combination of both. A total of 2 291 CV cases were retrieved, of which 1965 were related to ibrutinib, 312 to obinutuzumab, and 14 to the combination. Most cases referred to patients aged ≥ 65 years (N= 1,454; 63.47%) and male (N=1,497; 65.34%). Most cases were serious (N=2,131; 93.02%). The most reported events were: atrial fibrillation (N=913; 31.31%) and haemorrhage (N=201; 6.89%). A higher reporting frequency of CV events was found when ibrutinib was compared to obinutuzumab (ROR, 3.22; 95% CI, 2.89-3.60) or combination (ROR, 1.77; 95% CI, 1.11-2.83). A lower reporting was observed when obinutuzumab was compared to combination (ROR, 0.55; 95% CI, 0.34-0.88). A higher reporting frequency of CV events in patients exposed to ibrutinib ha formattato: Italiano (Italia) This is a provisional file, not the final typeset article in comparison with obinutuzumab was found. Further studies are needed to better explore the safety of ibrutinib.